2021
DOI: 10.1085/jgp.202012834
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent inhibition of BK channels by the opioid agonist loperamide

Abstract: Large-conductance Ca2+-activated K+ (BK) channels control a range of physiological functions, and their dysfunction is linked to human disease. We have found that the widely used drug loperamide (LOP) can inhibit activity of BK channels composed of either α-subunits (BKα channels) or α-subunits plus the auxiliary γ1-subunit (BKα/γ1 channels), and here we analyze the molecular mechanism of LOP action. LOP applied at the cytosolic side of the membrane rapidly and reversibly inhibited BK current, an effect that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…It has been previously reported that the antimotility effects of loperamide are inhibited by naloxone. 24,42 Since naloxone is non-selective and also acts at 𝛿 and κ receptors, a likely explanation Several in vitro [44][45][46] and ex vivo 47,48 human studies have suggested that the anti-diarrheal effect of loperamide may be mediated by naloxone-insensitive, non-opioid receptor pathways. The proposed mechanisms of action include antagonism of voltage-gated sodium or calcium channels and/or calmodulin inhibition, which primarily alter ion transport and secretory function rather than neuromuscular function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that the antimotility effects of loperamide are inhibited by naloxone. 24,42 Since naloxone is non-selective and also acts at 𝛿 and κ receptors, a likely explanation Several in vitro [44][45][46] and ex vivo 47,48 human studies have suggested that the anti-diarrheal effect of loperamide may be mediated by naloxone-insensitive, non-opioid receptor pathways. The proposed mechanisms of action include antagonism of voltage-gated sodium or calcium channels and/or calmodulin inhibition, which primarily alter ion transport and secretory function rather than neuromuscular function.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro 44–46 and ex vivo 47,48 human studies have suggested that the anti‐diarrheal effect of loperamide may be mediated by naloxone‐insensitive, non‐opioid receptor pathways. The proposed mechanisms of action include antagonism of voltage‐gated sodium or calcium channels and/or calmodulin inhibition, which primarily alter ion transport and secretory function rather than neuromuscular function.…”
Section: Discussionmentioning
confidence: 99%